Simplificar a expressão:sen(-x). cos(π/2 +x)/ tg(2π-x).cos(π-x)
Soluções para a tarefa
Respondido por
5
sen(-x) = -senx
cos(π/2+x) = -cos(π-π/2-x) = -cos(π/2-x)= -senx
tg(2π-x) = tg(-x) = -tgx
cos(π-x) = -cos(π-π+x) = -cosx
![\frac{sen(-x).cos( \frac{ \pi }{2}+x) }{tg(2 \pi -x)cos( \pi -x)} = \frac{-senx.(-senx)}{-tgx.(-cosx)}= \frac{senx.senx}{ \frac{senx}{cosx}.cosx } =senx \frac{sen(-x).cos( \frac{ \pi }{2}+x) }{tg(2 \pi -x)cos( \pi -x)} = \frac{-senx.(-senx)}{-tgx.(-cosx)}= \frac{senx.senx}{ \frac{senx}{cosx}.cosx } =senx](https://tex.z-dn.net/?f=+%5Cfrac%7Bsen%28-x%29.cos%28+%5Cfrac%7B+%5Cpi+%7D%7B2%7D%2Bx%29+%7D%7Btg%282+%5Cpi+-x%29cos%28+%5Cpi+-x%29%7D+%3D+%5Cfrac%7B-senx.%28-senx%29%7D%7B-tgx.%28-cosx%29%7D%3D+%5Cfrac%7Bsenx.senx%7D%7B+%5Cfrac%7Bsenx%7D%7Bcosx%7D.cosx+%7D+%3Dsenx+)
cos(π/2+x) = -cos(π-π/2-x) = -cos(π/2-x)= -senx
tg(2π-x) = tg(-x) = -tgx
cos(π-x) = -cos(π-π+x) = -cosx
Cecibl:
Mas por que o cos de 90-x deu -senx?
Perguntas interessantes
Biologia,
1 ano atrás
Inglês,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás